Mitigating CO2 Emission Via Catalytic Conversion to Methane : a Feasibility Study of Metal Oxide Supported Nickel Based Catalysts - Abu Seman, A; H. Berahim, N; G.M. Noh, M (International Journal of Engineering and Technology, 2019)
Exploration and production of sour gas field raise the need for CO2 management to minimize the adverse effect of green house gas venting to the environment. It is a fine balance between the sunken value of CO2 reinjection and value creation in CO2 conversion to value product, essential in ensuring projectâ€™s economic viability. Conversion to methane is selected due to the ease of integration with current process facility. Catalytic conversion of CO2 to methane are reported here over metal oxides (Al2O3, ZrO2 and La2O3) supported Nickel base catalysts over a range of temperature and GHSV with fixed H2/CO2 molar ratio. The catalysts were prepared by wet impregnation technique at room temperature. It was then characterized with X-Ray Diffraction (XRD), Brunauerâ€“Emmettâ€“Teller (BET), Temperature Programmed Reduction (TPR) and Temperature Programmed Desorption (TPD). All catalyst systems showed trend of decreasing CO2 conversion when the GHSV is increased from 10000 to 15000 h-1, which is in line with short reactant contact time. The impact is more pronounced at low temperature of 300 Â°C, but at high temperature of 400 Â°C, the conversion is almost comparable irrespective of GHSV. Experimental results indicate that Ni/Al2O3 gives the highest CO2 conversion of 74% while 7% and 67% for Ni/ZrO2 and Ni/La2O3 respectively. There is a prospect for further scaling up to complement the current commercial catalyst proven for handling low concentration of CO2.Â Â Â